Into the Vicious Cycle of Precarity: Labour Market, Precarious Work, Social Vulnerability and Youth: The case of Greece within the EU context - Papadakis, Nikos; Drakaki, Maria; Saridaki, Sofia; Dafermos, Vassilis (Advances in Social Sciences Research Journal, 2021)
Ιn the last decade, there has been a widespread expansion of both precarious work and precarious forms of employment (such as temporary and low- qualified jobs, seasonal and part-time jobs etc.), in which a growing share of young people work. The impact of precarious work on young people is likely to be permanent, while it seems to affect (even over-determine) their life courses. Non-smooth and early transitions into labour market are very likely to worsen progressively their long-term life chances (Lodovici & Semenza, 2012: 7). Undoubtedly, the long-lasting global economic Crisis and the subsequent Recession, has heavily affected the state of play in the labour market worldwide, provoking severe modifications both in the field of employment and countries’ social cohesion. Based on the above mentioned, the paper deals with precarious work in general, while it emphasizes precarious work among youth. It initially captures, briefly, the state of play in terms of the impact of the Crisis on the widening of the phenomenon of precarious work and then it focuses on theoretical insights and critical conceptual definitions concerning precariousness in the labour market. Further, based on secondary quantitative -data analysis, it analyses the key- parameters and facets of precarious work (focusing on youth) in the European Union and, mainly, in Greece. Additionally, it briefly presents parameters of the impact of the COVID-19 pandemic on precariousness in Greece. Finally, the paper explores the correlation between precarious work and social vulnerability, especially among young people. The present paper is based on an ongoing Research Project. More specifically, this research is co-financed by Greece and the European Union (European Social Fund- ESF) through the Operational Programme «Human Resources Development, Education and Lifelong Learning 2014-2020» in the context of the project “Precarious Work and Youth in today’s Greece: secondary quantitative analysis, qualitative filed research and research-based policy proposals” (MIS 5048510).